2018
DOI: 10.15653/tpg-180053
|View full text |Cite
|
Sign up to set email alerts
|

Das neu entdeckte „atypische porzine Pestivirus“ (APPV): ein alter Akteur im „Zitterferkelkrankheit“-Komplex?

Abstract: ZusammenfassungKongenitaler Tremor oder „Ferkelzittern“ bei neugeborenen Ferkeln ist ein altbekanntes Krankheitsbild unterschiedlicher Ätiologie und unterschiedlicher pathologischer Ausprägung. Neben nichtinfektiösen Ursachen (Intoxikationen, genetische Ursachen) spielen insbesondere virale Infektionen der Sau während der Gravidität ätiologisch eine bedeutende Rolle. Infektionen mit dem Virus der Klassischen Schweinpest, einem Pestivirus aus der Familie Flaviviridae, sind schon lange als mögliche Ursache von k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Soon thereafter, the virus was linked to congenital tremor type AII in piglets by Arruda et al [5] and others [2,3,6]. Since then, the virus has been described in a variety of countries, indicating that APPV is distributed worldwide [4,28,29]. In Switzerland, the first report of APPV in a sample from swine was found in a nasal swab analyzed by NGS by C. Bachofen in another project unrelated to pestiviruses (see Section 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soon thereafter, the virus was linked to congenital tremor type AII in piglets by Arruda et al [5] and others [2,3,6]. Since then, the virus has been described in a variety of countries, indicating that APPV is distributed worldwide [4,28,29]. In Switzerland, the first report of APPV in a sample from swine was found in a nasal swab analyzed by NGS by C. Bachofen in another project unrelated to pestiviruses (see Section 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, the duration of virus elimination in these pigs remains unknown. In addition, it was reported that several pigs with or without clinical signs of CT were still viremic at time of slaughter [2,3,4]. Therefore, the probability of finding virus-positive, older animals in breeding farms is expected to be rather low, as represented by the low prevalence in samples from 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation